Pawła Mayewskiego „Tematy” - Adamczyk, Kazimierz (Tematy i Konteksty, 2018)
The quarterly “Tematy”, edited by Paweł Mayewski, was published in the years 1961–1969. In 32 issues the editors published reprints of essayistic texts from elite American magazines, presenting works in the field of sociology, political science and literary criticism. There were also many translations poems of the greatest contemporary American poets. The eminent professors of American universities, as well as many Polish emigre writers, cooperated with Mayewski. Those appeared mainly in the role of translators. Mayewski’s magazine was part of the ideological offensive against communism and the place of presentation of the complex image of American society in the times of the Black people’s struggle for equality, student rebellion against the establishment, counterculture successes and at the same time the triumph of the consumerist model of society. All these issues as well as disputes among American intellectuals about the place of literature in the modern society found expression in the Mayewski’s quaterly. The sixties were a period of exhaustion of the potential of the New Critics’ school and the search for new ways of interpreting literary works. Also in this dimension, the quarterly addressed to the Polish reader has become a place for the presentation of new ideas.